Blockchain supported security functionality for internet of things (IoT) systems - Lee, Aik Leong (Nanyang Technological University, 2020)
As technology improves with the development of the internet. Entrepreneurs and innovator are finding new ways to improve the quality of life. Over the years, blockchain has started to develop in areas such banking, crowdfunding, and asset management. With the ease of access to development tools, developers can develop newer applications that would enhance the standards of living. However, at the same time, data could be easily access across the world with the advancement in technology. Therefore, there would be more reason to store data safely to prevent unwanted people from stealing/altering data. In this first part, I would be exploring ways to store data on to the blockchain, by using smart contracts and blockchain application.